The Concept of Protection of Land Rights Certificate Holders in Realizing Legal Certainty - Firmansyah, Arif; Jamilah, Lina; Irawati, Irawati (UNISSULA, 2025)
Land registration is carried out to regulate the legal relationship between the landowner and the land itself. Land registration has the aim of creating legal certainty. Landowners do land registration has a strong evidentiary tool that is in the form of a certificate of land rights. The intention of proving a strong land certificate is that the land certificate can still be cancelled, with the possibility of land certificates being cancelled; then, the cancellation harms the holder of land rights. In addition, people who have controlled the land for more than 20 years must be evicted due to losing the lawsuit for ownership rights. Hence, people who have utilized and maintained the land get losses because they cannot control the land anymore. The research method used is normative juridical with a statutory and conceptual approach. The result of this research is the Concept of Protection of Certificate Holders of land rights in realizing legal certainty is done by applying the Social Tenure Domain Model, acquisitive perjuring someone to get land with acquisitive verjaring for 20 years of controlling the land in good faith, rechtverwerking due to 20 years of not using and utilizing the land will be deprived of land rights. So, a person who has obtained a certificate of land rights is protected because the state guarantees it.